INTERNALISASI NILAI-NILAI PANCASILA DALAM MEMBENTUK KARAKTER SISWA MELALUI BUDAYA SEKOLAH - Rian Nurizka dan Abdul Rahim (Universitas PGRI Yogyakarta, 2020)
AbstractThis study aims to determine the internalization of the values of Pancasila in shaping the character of students based on school culture. The extent to which schools implement policies and programs in support of the inculcation of Â Pancasila values, the sustainability of the school culture in shaping the character of students, and evaluating the implementation of Pancasila internalization. This type of research is a descriptive qualitative research. This research can be classified in the field research category. Data collection used in this study uses observation, interview, and documentation techniques. Data analysis in this research is data collection, data reduction, data presentation, and drawing conclusions. The results showed that in shaping the character of students through school culture can be done with the School Physical Environment Arrangement, School Social Environment Arrangement, School Personnel Arrangement, School Work Environment Arrangement, Classroom Management, Principal Leadership.Keywords: Internalization of Â Pancasila values, Character, School culture